Electron-induced Ti-rich surface segregation on SrTiO3 nanoparticles. (January 2015) - Lin, Yuyuan; Wen, Jianguo; Hu, Linhua; McCarthy, James A.; Wang, Shichao; Poeppelmeier, Kenneth R.; Marks, Laurence D.
Highlights: Intense electron beam irradiation on SrTiO3 nanocuboids results in the formation of TiO and Ti islands on the surface. The structures of TiO and Ti islands were confirmed by aberration-corrected HREM, multislice simulation, and EELS. The Ti-rich surface is in agreement with previous theoretical and experimental predictions. Abstract: Atomic surface structures of nanoparticles are of interest in catalysis and other fields. Aberration-corrected HREM facilitates direct imaging of the surfaces of nanoparticles. A remaining concern of surface imaging arises from beam damage. It is important to identify the intrinsic surface structures and the ones created by electron beam irradiation in TEM. In this study, we performed aberration-corrected HREM and EELS to demonstrate that TiO and bcc type Ti islands form due to intense electron irradiation. The formation of Ti-rich islands is in agreement with previous high temperature annealing experiments on the surfaces of SrTiO3 single crystals.